Stretchable Full‐Color Phosphorescent PVA‐Based Ionogels for Multimodal Sensing‐Visual Integration Applications - Xuefeng Wei; Zexi Gou; Jianting Ye; L. H. Shi; Jianwei Zhao; Lei Yang; Linbo Zhang; Kun Zhang; Ruonan Jia (Advanced Science)
Abstract Exploring ionogels with superior conductivity, mechanical properties, and long‐lasting room temperature phosphorescence (RTP) offers considerable potential for new‐generation optoelectronics. However, reports on ionogels remain limited owing to the contradiction between the flexibility required for stretching and the rigidity necessary for RTP and load‐bearing within the same ionogels. Here, a facile strategy is reported to enhance the toughness and extend the RTP of ionogels by salting‐out‐induced microphase separation, which results in the formation of an IL‐rich phase (soft) for stretching and ionic conduction and a polymer‐rich phase (stiff) for energy dissipation and clustering‐triggered phosphorescence. The obtained ionogels exhibit high stretchability (≈400% strain), toughness (≈∼20 MJ m−3), ionic conductivity (8.4 mS cm−1), and ultralong afterglow lifetime (112.4 ms). This strategy is applicable to chromophores with color‐tunable phosphorescence. By leveraging observable full‐color RTP and real‐time electrical signals in response to diverse stimuli (i.e., stretching and pressing), an intelligent grasping strategy is developed for robust hand pose reconstruction. In addition, a tactile‐visual fusion recognition keyboard is created with dual functionality of information encryption and signal transmission. The ease of fabrication, wide tunability, and multifunctionality will help expand the scope of ionogels for smart devices.